Constructivism-based Instructional Style in Teaching and Learning Cultural Values - Olviani Cn. Tarinje (Sintuwu Maroso Journal of English Teaching, 2016)
Cultural values are important to be integrated in teaching and learning English. Under the paradigm of global literacy, it is important for EFL learners to express their cultural identity as local people by using English as global language. An appropriate instructional style is therefore considered as important factor in teaching and learning cultural values. This essay aims to discuss the importance of cultural values for EFL learners, and to propose a design of instructional style in teaching and learning cultural values based on constructivism theory.Keywords: cultural values, instructional style, constructivism, English